Exploration of the optimal retention method in vivo for stem cell therapy: Low-intensity ultrasound preconditioning - Haopeng Xu; Yilin Tang; Wenjing Mao; Liu Wu; Yiqing Zhou; Juan Deng; Wentao Tang; Xinfang Xiao; Yi Xia; Yan Wang (Regenerative Therapy)
Bone marrow mesenchymal stem cells (BMSCs) are pluripotent and self-renewing, exerting a crucial role in the domain of regenerative medicine. Nevertheless, BMSCs encounter challenges such as low cell viability and inadequate homing during transplantation, thereby restricting their therapeutic efficacy. Hence, current research is concentrated on identifying optimal retention approaches following BMSCs transplantation to enhance its effectiveness. Low-intensity ultrasound (LIUS) has been verified as an efficacious method to enhance the performance of BMSCs. We established a skin trauma model and assessed the therapeutic effect of LIUS-preconditioned BMSCs. The results demonstrated that pretreatment with LIUS could expedite wound healing and effectively diminish scar formation post-transplantation by promoting proliferation capacity, reinforcing anti-apoptotic attributes, improving homing ability, and significantly enhancing the transplantation effect of BMSCs. These discoveries imply that LIUS might constitute a promising strategy for attaining optimal retention after stem cell transplantation in regenerative medicine and wound repair therapy.